Enhanced net CO2 exchange of a semideciduous forest in the southern Amazon due to diffuse radiation from biomass burning - Rodrigues, Simone; Cirino, Glauber; Moreira, Demerval [UNESP]; Pozzer, Andrea; Palácios, Rafael; Lee, Sung-Ching; Imbiriba, Breno; Nogueira, José; Vitorino, Maria Isabel; Vourlitis, George (Copernicus Publications, 2024)
Carbon cycling in the Amazon fundamentally depends on the functioning of ecosystems and atmospheric dynamics, which are highly intricate. Few studies have hitherto investigated or measured the radiative effects of aerosols on the Amazon and Cerrado. This study examines the effects of atmospheric aerosols on solar radiation and their effects on net ecosystem exchange (NEE) in an area of semideciduous tropical forest in the north of Mato Grosso. Our results show that for a relative irradiance (f) 1.10-0.67, a decrease in incident solar radiation is associated with a reduction in the NEE. However, an average increase of 25%-110% in NEE was observed when pollution levels and aerosol optical depth (AOD) were above ≈1.25 and f<0.5. The increase NEE was attributed to the increase of up to 60% in the diffuse fraction of photosynthetically active radiation. The change in AOD and f was mainly attributable to biomass burning organic aerosols from fires. Important influences on vapor pressure deficit (VPD) as well as air temperature (Tair) and canopy (LCT), induced by the interaction between solar radiation and high aerosol load in the observation area, were also noticed. On average, a cooling of about 3-4 C was observed for Tair and LCT, and a decrease of up to 2-3hPa was observed for VPD. Given the long-distance transport of aerosols emitted by burning biomass, significant changes in atmospheric optical properties and irradiance will impact the CO2 flux of semideciduous forests distributed in the region.